Cementocyte-derived extracellular vesicles regulate osteoclastogenesis and osteoblastogenesis - Jiajun Li; Yukihiko Sakisaka; Eiji Nemoto; Kentaro Maruyama; Shigeki Suzuki; Kaixin Xiong; Hiroyuki Tada; Taichi Tenkumo; Satoru Yamada (Elsevier, 2024)
Background/purpose: Cementum shares many properties with bone; however, in contrast to bone, it is not innervated or vascularized and has a limited capacity for remodeling. Osteocytes located in the lacunae-canalicular system of bone tissue play a central role in bone remodeling by communicating with osteoblasts and osteoclasts. Although cementocytes are present in cellular cementum and are morphologically similar to osteocytes, it remains unclear whether they are involved in the dynamic functional regulation of metabolism in cementum. The present study focused on the extracellular vesicles (EVs) secreted by cementocytes and examined their effects on osteoclasts and osteoblasts. Materials and methods: EVs were extracted from the mouse cementocyte cell line, IDG-CM6. The effects of EVs on recombinant RANKL-induced osteoclastogenesis and recombinant Bone morphogenetic protein (BMP)-2-mediated osteoblastogenesis were investigated using the mouse osteoclast progenitor cell line, RAW264.7 and mouse pre-osteoblast cell line, MC3T3-E1, respectively. Results: EVs enhanced the formation of tartrate-resistant acid phosphatase activity-positive cells. Real-time PCR revealed that EVs up-regulated the expression of osteoclast-related genes. On the other hand, the cell culture supernatant of cementocytes significantly inhibited the differentiation of osteoclasts. Regarding osteoblastogenesis, EVs suppressed the expression of alkaline phosphatase, bone sialoprotein, and osteocalcin induced by recombinant BMP-2 at the gene and protein levels. Conclusion: A network of cementocytes, osteoblasts, and osteoclasts may exist in cellular cementum, which suggests the involvement of cementocytes in dynamic metabolism of cementum through EVs.